TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DAN TIPE THINK-PAIR-SHARE (TPS) PADA SISWA SMP - Suripah, Mrs. (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2015)
This study aimed to get empirical evidence about the effectiveness of STAD and TPS cooperative learning on junior high school studentsâ achievement and interest in mathematics. This study was a quasi- experimental research design with completely randomized factorial design. Sample were seventh grade students from two schools in Kebumen. The research instruments consisted of tests and interest questionnaire which contains questions and statement to determine the effectiveness of the learning model on studentsâ achievement and interest. The results showed that there was significant difference in achievement for STADA class (p = 0.046), STADB (p = 0.000), TPSA (p = 0.000), and TPSA (p = 0.042). In terms of interest, STAD and TPS significantly differed (p = 0.001, p <0.005). Multivariate analysis results show that there was interaction between learning model with the type of school (p = 0.001, p <0.005). It can be concluded that STAD andÂ TPS cooperative learningÂ were effective from the aspect of students achievement and interest in mathematics.Â ABSTRAKPenelitian Â ini Â bertujuan Â untuk Â memperoleh Â bukti Â empiris Â tentangÂ keefektifan Â model Â pembelajaran kooperatif tipe STAD dan TPS ditinjau dari aspek prestasi dan minat siswa SMP terhadap matematika. Penelitian ini adalah penelitian kuasi eksperimen dengan desain completely randomized factorial design. Sampel penelitian adalah siswa kelas VII dari dua sekolah yang ada di Kabupaten Kebumen. Instrumen penelitian Â terdiri Â atas Â tes dan Â angket Â minat Â yang berisi Â soal-soal Â uraianÂ danÂ item pernyataanÂ untuk mengetahui keefektifan model pembelajaran ditinjau dari aspek prestasi dan minat belajar siswa. Hasil penelitian menunjukkan bahwa terdapat perbedaan prestasi yang signifikan untuk kelas STADA (p= 0,046), STADB (p= 0,000), TPSA (p= 0,000), dan TPSA (p= 0,042). Pada aspek minat, kelas STAD dan TPS juga berbeda signifikan (p=0,001,). Hasil analisis Multivariat menunjukkan bahwa terdapat interaksi antara model pembelajaran dengan jenis sekolah Â (p=0,001). Dapat disimpulkan bahwa model pembelajaran kooperatif tipe STAD dan tipe TPS efektif ditinjau dari aspek prestasi maupun minat siswa terhadap matematika.